Travel motivations and constraints of Portuguese retirees - Filipe, Sandra (2022)
Retirees have been growing in importance as a consumer segment targeted by the tourism industry, namely because they can minimize the typical seasonality of tourism and increase its sustainability. This study aims to contribute to a more in-depth knowledge of retirees’ behaviour and has two objectives: (i) describe tourist behaviour of seniors prior to and after retirement; (ii) identify and analyse retired consumers’ current motivations and constraints towards tourism. Qualitative research was conducted comprising interviews with 40 Portuguese retirees. The results indicate a diversity of experiences regarding tourism activities both before and after retirement, evidencing that past experience stands out as a determinant of retirees’ tourism behaviour. Moreover, three distinct segments of tourists emerge: the experts, the new tourists, and the non-tourists.